2021
DOI: 10.1097/olq.0000000000001373
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of HIV Preexposure Prophylaxis Adherence Among Female Sex Workers in a Demonstration Study in Cotonou, Benin: A Study of Behavioral and Demographic Factors

Abstract: A study of demographic and behavioral factors found that older age, high intention, and shorter duration of preexposure prophylaxis use were associated with higher preexposure prophylaxis adherence among Beninese female sex workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…We also found that female sex workers aged between 18 and 25 years had an increased risk of early disengagement from PrEP services compared with those aged above 35. This finding corroborates earlier evidence that higher age predicts consistent PrEP use25 26 and is likely related to factors ranging from the individual to the structural level (neurocognitive development, peer influence, socioeconomic and structural vulnerabilities, etc) 58. Health services need to be particularly considerate when encountering young women who sell sex, ensuring that they experience friendly services and providers that are suitably trained on their needs.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We also found that female sex workers aged between 18 and 25 years had an increased risk of early disengagement from PrEP services compared with those aged above 35. This finding corroborates earlier evidence that higher age predicts consistent PrEP use25 26 and is likely related to factors ranging from the individual to the structural level (neurocognitive development, peer influence, socioeconomic and structural vulnerabilities, etc) 58. Health services need to be particularly considerate when encountering young women who sell sex, ensuring that they experience friendly services and providers that are suitably trained on their needs.…”
Section: Discussionsupporting
confidence: 84%
“…The factors explored in this study are situated in different layers of the socioecological model, although several factors can be seen as belonging to more than one layer. At the individual level, studies have shown that older age at PrEP initiation can predict continuation among female sex workers,25 26 while high self-perceived HIV risk has been linked to PrEP uptake and continuation 27. Often referred to as psychosocial factors, poor mental health and alcohol use have been linked to adherence to or continuation with PrEP 25 26.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of FSW in most countries point to chronic unstable housing and financial insecurity, which may lead to challenges in sustained PrEP adherence. [24][25][26] Lastly, it is important to acknowledge the importance of social status, power, control, and education in the demand for PrEP. Compared to FSW in Britain, health issues are perceived as less important and FSW face fewer challenges with safe work spaces, violence, and control over interactions with clients.…”
Section: Discussionmentioning
confidence: 99%
“…[13] However, despite the high risk of HIV acquisition among FSWs, most studies on PrEP adherence among FSWs have revealed minimal compliance with the provided prophylaxis. [14][15][16][17] Literature on adherence to HIV oral PrEP is limited. This study aims to determine adherence and factors associated with non-adherence to oral HIV PrEP by gathering information related to the extent to which FSWs receive the PrEP service in the Mara region.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%